Urinary Kidney Injury Molecule-1 An Early Diagnostic Marker of Acute Kidney Injury in Patients Undergoing Coronary Artery Bypass Grafting - Divya Dharshini B; Ganesh M; Smita Padhy; Silambanan Santhi; Girijavani DSS (International Journal of Pharma and Bio Sciences, 2023)
Acute kidney injury(AKI) is a rapid decline in glomerular function rate(GFR) and its diagnosis is currently based on functional biomarkers, serum creatinine, and blood urea nitrogen which are not very specific and sensitive. Among many potential noninvasive AKI biomarkers, KIM-1 is one of them. CABG, which employs cardiopulmonary bypass, is the most common cause of acute kidney injury. Aim of the study was to find the role of urinary KIM-1 as an early diagnostic marker of AKI in patients who have undergone CABG and objectives were assessed by measuring Urinary KIM-1, 6 hours post CABG to identify it as an early diagnostic marker of AKI. It’s a cross-sectional study carried out at Sri Ramachandra Medical College and Research Institute. It includes 80 patients aged between 30-60 years and undergoing CABG. Urinary KIM-1 was measured 6 hours and Serum creatinine was measured 48 hours post-CABG. Out of 80, 10 patients developed AKI, and 70 patients did not develop AKI. Urinary KIM-1 and serum creatinine measured in AKI and non-AKI patients were analysed using SPSS software 16.0. The mean ± SD of urinary KIM-1 in patients with AKI was 5.936±2.002, which was significantly higher (p<0.0001) than patients who did not develop AKI. Mean ± SD of serum creatinine in patients with AKI was significantly higher(P<0.0001) than patients who did not develop AKI. This study showed significantly higher concentrations of urinary KIM-1, 6 hours Post-CABG patients who developed AKI, making it an early biomarker for diagnosis of acute kidney injury in them.